Calcium-Doped Boron Nitride Aerogel Enables Infrared Stealth at High Temperature Up to 1300 °C - Zhu, Mengya; Li, Guangyong; Gong, Wenbin; Yan, Lifeng; Zhang, Xuetong (Nano-Micro Letters, 2021)
Boron nitride (BN) aerogels, composed of nanoscale BN building units together with plenty of air in between these nanoscale building units, are ultralight ceramic materials with excellent thermal/electrical insulation, great chemical stability and high-temperature oxidation resistance, which offer considerable advantages for various applications under extreme conditions. However, previous BN aerogels cannot resist high temperature above 900 °C in air atmosphere, and high-temperature oxidation resistance enhancement for BN aerogels is still a great challenge. Herein, a calcium-doped BN (Ca-BN) aerogel with enhanced high-temperature stability (up to 1300 °C in air) was synthesized by introducing Ca atoms into crystal structure of BN building blocks via high-temperature reaction between calcium phosphate and melamine diborate architecture. Such Ca-BN aerogels could resist the burning of butane flame ( 1300 °C) and keep their megashape and microstructure very well. Furthermore, Ca-BN aerogel serves as thermal insulation layer, together with Al foil serving as both low-infrared-emission layer and high-infrared-reflection layer, forming a combination structure that can effectively hide high-temperature target (heated by butane flame). Such successful chemical doping of metal element into crystal structure of BN may be helpful in the future design and fabrication of advanced BN aerogel materials, and further extending their possible applications to extremely high-temperature environments. Highlights: 1 A calcium-doped boron nitride (Ca-BN) aerogel was synthesized by introducing Ca into crystal structure of BN building blocks. 2 The aerogels exhibited superior high-temperature stability and could resist the burning of butane flame ( 1300 °C) in air atmosphere. 3 Ca-BN aerogel, together with Al foil, can effectively hide thermal target at high temperature up to 1300 °C.